PENGARUH TATA KELOLA PERUSAHAAN DAN KETERLAMBATAN PELAPORAN KEUANGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Meilani, Sylvi; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2024)
This research aims to determine the size of the board of commissioners, the proportion of independent commissioners, the audit committee, institutional ownership, disclosed ownership, managerial ownership, and delays in financial reporting that can have an influence on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2019–2022. By measuring financial performance, companies can make improvements and control operational activities in accordance with company conditions so that they are able to compete with other companies. In addition, performance is measured to help determine the right strategy to achieve company goals.This research is empirical research that describes and explains the influence of the phenomenon that is the object of research. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2019–2022 period. In this research, researchers used a purposive sampling method to obtain research samples. The number of samples used in this research was 4, with a total of 16 research data points.The research results show that the size of the board of commissioners, the proportion of independent commissioners, the audit committee, institutional ownership, concentrated ownership, managerial ownership, and delays in financial reporting do not have a significant influence on the company's financial performance, whether measured by return on assets (ROA) or return on equity (ROE).